A Comparative Economic Study on BARI GOM-24 and BARI GOM-23 Production in a Selected Area of Dinajpur District (Progressive Agriculture, 2013)
This study was designed to determine the costs, returns and relative profitability of BARI GOM-24 and BARI GOM-23 production in Dinajpur district. In total 60 farmers were selected of whom 30 produced BARI GOM-23 and 30 produced BARI GOM-24 from two villages of Khanshama Upazila of Dinajpur district. Cost-return and functional analyses were done to achieve the objectives of the study. It was revealed that the cultivation of both BARI GOM-24 and BARI GOM-23 were profitable for the farmers. Per hectare gross cost of production of BARI GOM-23 and BARI GOM-24 were Tk. 49898.54 and Tk. 54104.15, respectively and the corresponding gross returns were Tk. 77715.02 and Tk. 65608.44. The per hectare net returns of producing of BARI GOM-23 and BARI GOM-24 were Tk. 27816.48 and Tk. 11504.29, respectively. The results indicated that BARI GOM-24 was more profitable than BARI GOM-23. Cobb-Douglas production function was applied to address the effects of individual inputs on gross return of BARI GOM-24 and BARI GOM-23. It was observed that most of the included variables had significant impact on gross return from BARI GOM-24 and BARI GOM-23 production and gross return could be increased further by increasing the use of some inputs like human labour, seed and fertilizer. The study also identified some problems faced by the producers in producing BARI GOM-24 and BARI GOM-23. Based on the findings of the study, some recommendations were made to improve the cultivation and management practices for BARI GOM-24 and BARI GOM-23 farming in order to increase the income of the farmers.DOI: http://dx.doi.org/10.3329/pa.v23i1-2.16576Progress. Agric. 23(1 & 2): 123 132, 2012